On the Spin Liquid States of the Fermionized Heisenberg Antiferromagnetic on Triangular Lattice - Nga, Pham Thi Thanh; Thang, Nguyen Toan (Communications in Physics, 2012)
We have analyzed the spin-1/2 isotropic Heisenberg antiferromagnetic system on triangular lattice within Popov--Fedotov functional intergral formalism when the spin operators are represented by the fermionic ones and the constraint of single occupancy conditions is taken into account by introducing an imaginary chemical potential. We study the effect of site occupation in quantum spin systems on the triangular lattice at finite temperature in a spin liquid states.